Geochemical challenge to earthquake prediction. - Wakita, H (1996)
The current status of geochemical and groundwater observations for earthquake prediction in Japan is described. The development of the observations is discussed in relation to the progress of the earthquake prediction program in Japan. Three major findings obtained from our recent studies are outlined. (i) Long-term radon observation data over 18 years at the SKE (Suikoen) well indicate that the anomalous radon change before the 1978 Izu-Oshima-kinkai earthquake can with high probability be attributed to precursory changes. (ii) It is proposed that certain sensitive wells exist which have the potential to detect precursory changes. (iii) The appearance and nonappearance of coseismic radon drops at the KSM (Kashima) well reflect changes in the regional stress state of an observation area. In addition, some preliminary results of chemical changes of groundwater prior to the 1995 Kobe (Hyogo-ken nanbu) earthquake are presented.